Orchestral Characteristic of The English Lecturer Based on The Students’ Perception at English Education Study Program of Cokroaminoto Palopo - Rizal A.M. Sjachrun; Edi Wahyono; Muhammad Hasby (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
The main objective of this study was to describe the Orchestral Characteristic of English lecturer based on the students’ perception at English Education Study Program of Cokroaminoto Palopo University: (1) to describe the orchestral characteristic of English lecturer based on the students’ perception at English Education Study Program of Cokroaminoto Palopo University, (2) to describe the way to own the orchestral characteristic of English lecturer based on the students’ perception at English Education Study Program of Cokroaminoto Palopo University. This research employed Descriptive Qualitative Method. The research participants involved in this research is 7 students. The data were collected through interview, video and tape recording, and note. All the data are analyzed qualitatively. The result showed that: first, the description of Orchestral Characteristics of English lecturer based on the students’ perception at English Education Study Program of Cokroaminoto Palopo University. Secondly, there are five factors which determine the existence of this characteristic namely Assignment, Knowledge, Assessment, Learning and Teaching Strategy and Material Approach Factor. The study presents a theoretical implication towards orchestral characteristics which has close relation to the teaching process in language learning.